The Impact of Externally Worn Diabetes Technology on Sexual Behavior and Activity, Body Image, and Anxiety in Type 1 Diabetes. (March 2020) - Robertson, Courtney; Lin, Ashleigh; Smith, Grant; Yeung, Anna; Strauss, Penelope; Nicholas, Jennifer; Davis, Elizabeth; Jones, Tim; Gibson, Lisa; Richters, Juliet; Bock, Martin de
Background: We aimed to explore the impact of externally worn diabetes technologies on sexual behavior and activity, body image, and anxiety in adopters and nonadopters of these devices. Methods: People with type 1 diabetes aged 16-60 years living in Western Australia were invited to complete an online survey. Results: Of the 289 respondents (mean age 34.3 years), 45% used continuous subcutaneous insulin infusion (CSII) and 35% used continuous glucose monitoring (CGM). Approximately half of CSII users stated that the pump interferes with sex. Of these, 75% disconnect their pump during sexual activity to avoid this issue. Comfort during sex influenced the location of the CSII insertion site in 22% of respondents, with the abdomen being preferred. One in four non-CSII users cited sex-related concerns as a factor for not adopting the technology. CGM interfered with sexual activity in 20% of users, but did not commonly affect CGM placement (only 18%). Sexual activity was reported as a factor for not adopting the technology in 10% of non-CGM users. No differences in body dissatisfaction ( P = .514) or anxiety ( P = .304) between CSII and non-CSII users were observed. No differences in sexual activity and behavior between technology users and nontechnology users were observed. Conclusion: Wearable technologies impact upon sexual activity and this influences the decision to adopt the technology. Despite this, technology users are similar in terms of sexual behavior, anxiety, and body image compared to nontechnology users. Where appropriate, these data can be used to identify potential concerns, address strategies to mitigate them, and inform people with diabetes when considering adopting external technologies.